Biometric Characterization and Morphophysiological Quality of Peach Rootstock Seeds Using Images of their Seedling Vigor - Souza, Aline G.; Smiderle, Oscar J.; Bianchi, Valmor J. (Recent Patents on Food, Nutrition & Agriculture, 2018)
Background: This study aimed to evaluate the efficiency of using the computerized imaging Seed Analysis System (SAS) in the biometric and morphophysiological characterization of seeds and the initial growth of seedlings from peach rootstocks. Methods: The experimental design was completely randomized with five replicates of 20 seeds. The variables analyzed were the seed humidity content, length and width of seeds measured by SAS technology and manual measurements, mean germination time, germination percentage, radicle length and width, taproot length, length of the aerial part and taproot/aerial part ratio. Results: The highest seed length, germination percentage (100%) and lower germination time (11.3), were obtained with the cv. Capdeboscq while, ‘Tsukuba 1’, 2' and 3' had intermediate seedlings length, varying from 1.55 to 1.65 cm with mean germination times between 14.5 and 18.0 days and average germination percentage of 96%. The computerized analysis of images is fast and efficient for biometric evaluations such as seed width and length, as well as initial growth of peach tree seedlings. The cvs Capdeboscq, Flordaguard and Tsukuba 2 presented greater radicle width, length and a mean taproot/aerial part ratio equal to 2, as well as higher number of adventitious roots, which indicated a strong positive correlation between radicle length, taproot length and initial seedling growth. Conclusion: The continuity of the research will certainly allow the development of reliable procedures for other species, besides allowing the identification of wider alternatives for the use of this system for the expansion of knowledge in the areas of physiology and evaluation of the physiological potential of seeds.
Keywords: correlation